Public Service Effectiveness and Taxpayer Satisfaction in a Social Governance Perspective - Hutahaean, Sarah Ayu; Rahawarin, Mohamad Arsad; Soselisa, Pieter Sammy (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to analyze the effect of service effectiveness on taxpayer satisfaction at the Regional Revenue Agency of Maluku Province, specifically in Motor Vehicle Tax payment services at One-Stop Administration Services Office Waihaong Ambon. The research positions taxpayer satisfaction not only as an administrative performance indicator but also as a reflection of governance quality, institutional legitimacy, and the relational dynamics between government and citizens within a decentralized public administration framework. Methodology: This study employed a quantitative survey approach involving taxpayers who directly accessed Motor Vehicle Tax payment services. Respondents were selected using an incidental sampling technique based on their direct service experience. Data were collected through structured Likert-scale questionnaires measuring service effectiveness (service speed, procedural accuracy, clarity of information, accessibility, and officer professionalism) and taxpayer satisfaction. Instrument validity and reliability tests were conducted prior to analysis. Data were analyzed using descriptive statistics and simple linear regression with SPSS software, including hypothesis testing (t-test) and coefficient of determination (R²). Main Findings: The findings indicate that service effectiveness has a positive and statistically significant effect on taxpayer satisfaction. The regression results demonstrate that improvements in service speed, procedural clarity, accessibility, and officer professionalism directly increase satisfaction levels. The coefficient of determination shows that service effectiveness explains a substantial proportion of variance in taxpayer satisfaction. These results confirm that effective public service delivery not only enhances citizen satisfaction but also strengthens public trust, perceptions of administrative fairness, and institutional legitimacy in regional tax administration. Novelty/Originality of this study: This study contributes new empirical evidence from an archipelagic regional context in eastern Indonesia by integrating a quantitative service effectiveness model with a social governance perspective. Unlike prior studies that primarily emphasize technical service quality dimensions, this research conceptualizes taxpayer satisfaction as an indicator of institutional trust and governance legitimacy. The study enriches public administration literature by demonstrating how frontline service performance influences broader governance outcomes within decentralized regional tax systems.